Skills In Playing Football Of The Fifth Grade Students Of Sdn Wonolopo 03, Semarang City - Malik, Ryan Ridho (Jurnal Pendidikan Dasar dan Aktifitas Jasmani, 2025)
The objective of the research is to find out how the skills in playing football of the fifth grade V students of SDN Wonolopo 03 (Wonolopo 3 Elementary School), Semarang City.This research was a descriptive quantitative study. The research subjects were the fifth grade students of SDN Wonolopo 03, Semarang City, totaling 27 students. The research method was a survey method with a football skill test instrument from Daral Fauzi (2009) for the children aged 10-12 years old. To determine the level of football skills using six test items: 1) dribbling, 2) short pass, 3) throw in, 4) running with the ball, 5) heading, and 6) shooting at the goal. The data analysis technique used the descriptive quantitative analysis.The results show that the level of football skills of the fifth grade students of SDN Wonolopo 03 is in various levels: in the very high level is at 0%, in the high level is at 0%, in the medium level for about 9 students or at 33.33%, in the low level for about 8 students or at 29.63%, and in the very low level for about 10 students or at 37.04%. From the research results it can be seen that the highest percentage is in the very low level at 37.04%.